Interfaces gráficas em visualização de informação : modelo conceptual para o design de informação espaço-temporal interativa - Rodrigues, Sara (2021)
This research describes the design process for interactive spatio-temporal information visualization by recognizing the requirements, factors, and dimensions of its graphical interface. Spatio-temporal visualization allows the user to observe, interpret, and understand events by locating them in time and space. When interactive, spatio-temporal visualization promotes exploration, discovery, and analysis of complex phenomena.This dissertation consists of two parts. The first one is based on the review anddiscussion of the reference literature and introduces the research question inits scientific area and design processes. First, "information visualization" is contextualized historically and conceptually. Subsequently, the research object, "interactive spatio-temporal visualization", is defined through the classification of its components and the identification of the intricacies of projects of this kind. In the second part – the operational section – we apply the case study method and analyze the main techniques practiced in a set of reference visualizations. Throughout this study, it was noticed that the spatio-temporal context requires specific multidimensional interaction functionalities. Therefore, a second approach of the same method focuses exclusively on interactivity, encompassing the potentials and limitations of interaction with Time and Space. This procedure results in a proposed new taxonomy for spatio-temporal interaction. Finally, we outline a conceptual model for interactive spatio-temporal information visualization, which involved the collaboration of three experts. The outcome classifies and systematizes the creative process by organizing the inherent design decisions into requirements, factors, and dimensions. The research concludes with one hypothesis of validation of the proposed conceptual model through its application in a visualization chosen by a fourth expert. The proposal of a theoretical tool that reflects the multidisciplinar and iterative properties of the design process contributes to the mitigation of boundaries between design practice and research.